PENANAMAN KARAKTER NASIONALIS BAGI PELAJAR DAN MAHASISWA PENGUNJUNG MUSEUM KAMBANG PUTIH DI KABUPATEN TUBAN - Rizqiyah, Nazilatur; Jatiningsih , Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
This research describes the efforts made by the management of the Kambang Putih Museum to instill a nationalist character in students and college students as museum visitors and the challenges they face. This research uses qualitative research methods with a case study research design. This research is limited to the management of the Kambang Putih Museum in 2023. The informants for this research are museum managers, pupils and students who have been participants in activities at the Kambang Putih Museum. Data collection techniques used observation, in-depth interviews, and documentation with Miles and Huberman data analysis techniques. This research is linked to Thomas Lickona's character education theory. The results of this research show that, four efforts have been made by museum managers, namely holding Learning Together with the Museum (BBM), holding museum collection study activities, holding art collection competitions, and accompanying school or campus visits. Through these efforts, pupils and students can learn about history, culture and diversity which can form a nationalist character. In carrying out these efforts, only bureaucratic problems are a challenge for museum managers. However, this does not become an obstacle in implementing existing activities. Museum managers already have a solution to face challenges related to bureaucracy, namely by communicating frequently with the Department of Tourism, Culture, Youth and Sports. Through the efforts made by the museum management, nationalist values ??such as being willing to sacrifice for the sake of the nation, respecting ethnic, cultural and religious diversity, respecting and preserving the nation's culture, and love of the homeland.